A Composite Biomarker of Derived Neutrophil–Lymphocyte Ratio and Platelet–Lymphocyte Ratio Correlates With Outcomes in Advanced Gastric Cancer Patients Treated With Anti-PD-1 Antibodies - Pan, Yuting; Si, Haiyan; Deng, Guochao; Chen, Shiyun; Zhang, Nan; Zhou, Qian; Wang, ZhiKuan; Dai, Guanghai (Frontiers in Oncology, 2022)
Background The highly heterogeneous characteristics of GC may be limit the accuracy of a single biomarker for screening populations benefiting from immunotherapy. However, the combination of multiple indicators can provide more directed information for the detection of potential immune benefit subgroups. At present, there are no recognized complex indexes to identify advanced GC (AGC) in patients who are likely benefited from immunotherapy. The objective of this research is to explore whether the composite biomarker of derived neutrophil-lymphocyte ratio (dNLR) and platelet-lymphocyte ratio (PLR) can be used as a reliable prognostic factor for the survival of AGC patientst receiving immunotherapy. Methods A total 238 AGC patients at a single Center were included in this retrospective cohort research study. The cut-off value of dNLR was obtained by the ROC curves to predict the disease progression rate at the 8th month and the cut-off value of PLR was estimated by the median value. The cut-off values of dNLR and PLR were 1.95 and 163.63, respectively. The high levels of dNLR(≥1.95) and PLR (≥163.63) were considered to be risk factors. Based on these two risk factors, patients were categorized into 3 groups: the risk factor number for the "good" group was 0, for the "intermediate" group was 1, and for the "poor" group was 2. The subjects were divided into two groups: dNLR/PLR-good and dNLR/PLR-intermediate/poor. Results The median overall survival (mOS) and progression free survival (mPFS) were 12.5 and 4.7 months, respectively. The intermediate/poor dNLR/PLR group was independently correlated with an over 1.4 times greater risk of disease progression (4.1 months vs 5.5 months; P =0.016) and an over 1.54 times greater risk of death (11.1 months vs 26.3 months; P=0.033) than the good dNLR/PLR group. However, no clear differences of the disease control rate（DCR）and overall response rate (ORR) were observed between the intermediate/poor dNLR/PLR group and the good dNLR/PLR group (51.5% vs 56.3%, 26.3% vs 29.6% ; P =0.494, P=0.609).